RECONSTRUCTION TECHNIQUES OF UPPER AND LOWER EYELID FULL THICKNESS DEFECTS: TEN-YEAR SINGLE CENTER EXPERIENCE - Meryem Altın Ekin; Şeyda Karadeniz Uğurlu (İstanbul Tıp Fakültesi Dergisi)
Objective: To evaluate long term outcomes of reconstruction techniques used for full thickness defects of upper and lower eyelids. Material and Method: Patients who had undergone reconstruction for full thickness eyelid defects were evaluated retrospectively. Partial thickness defects, defects which were less than 1/3 of the total size of the eyelid, and defects which could be repaired primarily without flap were excluded from the study. Surgical borders were excised with negative margins in malignant tumors. Reconstruction methods were performed according to the size and localization of eyelid defects. Demographic characteristics of patients, etiologies, reconstruction methods, sizes of the defects, pathology reports, follow-up times, postoperative complications, tumor recurrence, and surgical outcomes were recorded. Patients were evaluated for surgical outcomes, complications and tumor recurrence. Results: Eighty-four eyes of eighty-two patients were included in the study. The mean age was 67.5±13.5 years. The mean follow-up time was 21.2±14.6 (3-80) months. Reconstruction of lower eyelid was perfomed in 63 (75%) patients, upper eyelid in 18 (21.4%) patients and both lower and upper eyelid in 3 (3.6%) patients. Basal cell carcinoma was diagnosed in 65.4% (n=55) of patients. Reconstruction was performed using only flap in 74 (88.1%) patients and flap and graft in 10 (11.9%) patients. Among 15 (17.9%) patients with complications, 5 (5.9%) underwent secondary surgery. Cosmetic and functional outcomes were satisfactory in 95.2% and 96.4% of patients, respectively. Tumor recurrence was not observed during follow-up.Conclusion: In the full thickness defects of upper and lower eyelids, good functional and cosmetic outcomes can be achived using proper reconstruction methods.